INFLUENCE OF HUSBAND SUPPORT AND PARITY AGAINST THE INCIDENCE OF DROP OUT KB INJECTION 3 MONTH AT PAMEKASAN - Purmahardini, Nova; Peristiowati, Yuly; Suhita, Byba Melda (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Rapid population growth in Indonesia has prompted the government to launch the Family Planning (KB) program in order to reduce the birth rate. This research was conducted to find out what factors influenced the incidence of drop out of 3 month injection contraceptive in pamekasan and analyzed the most dominant factor on the incidence of drop out Kb injection 3 months at puskesmas proppo pamekasan district (BKKBN, 2013) The research design in this research is analytical survey with cross sectional approach. Population in this research is all acceptor drop out KB injection 3 month in Pamekasan, with technique. cluster sampling obtained a sample of 149 KB injectors who dropped out in Pamekasan. Data processing with Editing, Coding and Tabulating. The analysis technique used is ordinal regression analysis using SPSS v.23 for windows.The results of this study indicate that the support of husbands, knowledge there is an effect on the incidence of drop out KB inject 3 months in pamekasan. The most dominant factor on the incidence of drop out injecting KB 3 months in pamekasan is the factor of support of husbands with the effect of 8,707 times. Keywords: support of husband, knowledge and event of drop out KB injection 3 months.